Comparing the Rates of Retinal Nerve Fiber Layer and Ganglion Cell–Inner Plexiform Layer Loss in Healthy Eyes and in Glaucoma Eyes - Hammel, Naama; Belghith, Akram; Weinreb, Robert N.; Medeiros, Felipe A.; Mendoza, Nadia; Zangwill, Linda M. (American journal of ophthalmology, 2017)
To compare the rates of circumpapillary retinal nerve fiber layer (RNFL) and macular retinal ganglion cell–inner plexiform layer (GCIPL) change over time in healthy and glaucoma eyes. Cohort study. The rates of circumpapillary RNFL and macular GCIPL loss in 28 healthy subjects and 97 glaucoma subjects from the Diagnostic Innovations in Glaucoma Study (DIGS) were compared using mixed-effects models. The median follow-up time and number of visits were 1.7 years and 6 visits and 3.2 years and 7 visits for healthy and glaucoma eyes, respectively. Significant rates of loss of both global circumpapillary RNFL and average macular GCIPL thickness were detectable in early and moderate glaucoma eyes; in severe glaucoma eyes, rates of average macular GCIPL loss were significant, but rates of global circumpapillary RNFL loss were not. In glaucoma eyes, mean rates of global circumpapillary RNFL thickness change (−0.98 μm/year [95% confidence interval (CI), −1.20 to −0.76]) and normalized global circumpapillary RNFL change (−1.7%/year [95% CI, −2.1 to −1.3]) were significantly faster than average macular GCIPL change (−0.57 μm/year [(95% CI, −0.73 to −0.41]) and normalized macular GCIPL change (−1.3%/year [95% CI, −1.7 to −0.9]). The rates of global and inferior RNFL change were weakly correlated with global and inferior macular GCIPL change (r ranges from 0.16 to 0.23, all P < .05). In this cohort, the rate of circumpapillary RNFL thickness change was faster than macular GCIPL change for glaucoma eyes. Global circumpapillary RNFL thickness loss was detectable in early and moderate glaucoma, and average macular GCIPL thickness loss was detectable in early, moderate, and severe glaucoma, suggesting that structural changes can be detected in severe glaucoma.